A New Report on Edible Tropical Bolete, Phlebopus spongiosus in Thailand and Its Fruiting Body Formation without the Need for a Host Plant. Issue 4 (3rd July 2020) - Kumla, Jaturong; Suwannarach, Nakarin; Lumyong, Saisamorn
Abstract: Phlebopus spongiosus is a well-known edible ectomycorrhizal mushroom indigenous to southern Vietnam. The mushroom specimens collected from northern Thailand in this study were identified as P . spongiosus . This identification was based on morphological characteristics and the multi-gene phylogenetic analyses. Pure cultures were isolated and the relevant suitable mycelial growth conditions were investigated. The results indicated that the fungal mycelia grew well on L-modified Melin-Norkans, and Murashige and Skoog agar all of which were adjusted to a pH of 5.0 at 30 °C. Sclerotia-like structures were observed on cultures. The ability of this mushroom to produce fruiting bodies in the absence of a host plant was determined by employing a bag cultivation method. Fungal mycelia completely covered the cultivation substrate after 90–95 days following inoculation of mushroom spawn. Under the mushroom house conditions, the highest amount of primordial formation was observed after 10–15 days at a casing with soil:vermiculite (1:1, v/v). The primordia developed into a mature stage within one week. Moreover, identification of the cultivated fruiting bodies was confirmed by both morphological and molecular methods. This is the first record of P . spongiosus found in Thailand and its ability to form fruiting bodies without a host plant.